A história da pós-graduação em Biblioteconomia no Brasil: a interação texto/contexto - Alcenir Soares dos Reis (1990)
This study recovers the history of the five Brazilian Post-Graduate Programmes on Library Science: Instituto Brasileiro de Bibliografia e Documentação - IBBD, now called Instituto Brasileiro de Informação em Ciência e Tecnologia - IBICT, Universidade Federal de Minas Gerais - UFMG, Pontificia Universidade Católica de Campinas - PUCCAMP, Universidade de Brasília - UnB and Universidade Federal da Paraíba - UFPb. The methodoly was directed to critically aprehend the underlyng facts in the implementation of the above-mentioned programmes. To make it effective, the study was based on the literature, on the recollections of the subjects about the historical facts and on official documentation. The results show that these Programmes were created to meet demands from the actual context, especially in relation to educational policy and to Coordenação do Aperfeiçoamento de pessoal de Nível Superior - CAPES tutoring of the profissional market demands. The institutionalization of those educational programmes had the objective of modernization and development, characteristics of the social context.